2020
DOI: 10.3389/fchem.2020.00404
|View full text |Cite
|
Sign up to set email alerts
|

TADF Dye-Loaded Nanoparticles for Fluorescence Live-Cell Imaging

Abstract: Thermally activated delayed fluorescence (TADF) molecules offer nowadays a powerful tool in the development of novel organic light emitting diodes due to their capability of harvesting energy from non-emissive triplet states without using heavy-metal complexes. TADF emitters have very small energy difference between the singlet and triplet excited states, which makes thermally activated reverse intersystem crossing from the triplet states back to the singlet manifold viable. This mechanism generates a long-liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…This is in line with what has been reported previously (Crucho et al, 2020;Okkelman et al, 2020). The third, and most long-lived decay phase, is attributed to PF from DPTZ-DBO2 nanoparticles, in line with the observation by Crucho et al, 2020, who reported a very similar PF lifetime for the same type of DPTZ-DBO2 nanoparticles (Crucho et al, 2020). Consequently, we cannot claim there is a DF component in the emission from DPTZ-DBO2 nanoparticles internalised in NIH 3T3 cells, based on the fit of the data in Figure 5.…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…This is in line with what has been reported previously (Crucho et al, 2020;Okkelman et al, 2020). The third, and most long-lived decay phase, is attributed to PF from DPTZ-DBO2 nanoparticles, in line with the observation by Crucho et al, 2020, who reported a very similar PF lifetime for the same type of DPTZ-DBO2 nanoparticles (Crucho et al, 2020). Consequently, we cannot claim there is a DF component in the emission from DPTZ-DBO2 nanoparticles internalised in NIH 3T3 cells, based on the fit of the data in Figure 5.…”
Section: Resultssupporting
confidence: 94%
“…In this part of the work, we also investigated polystyrene nanoparticles containing the TADF emitter DPTZ-DBTO2, internalised in NIH 3T3 cells. The application of these nanoparticles in bioimaging was also described by Crucho et al, 2020 , but for MCF-7 cells. Confocal images of DPTZ-DBTO2 nanoparticles in NIH 3T3 cells can be found in the SI ( Supplementary Figure S5 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations